Standardization of the [68Ga]Ga-PSMA-11 Radiolabeling Protocol in an Automatic Synthesis Module: Assessments for PET Imaging of Prostate Cancer - Leonardo L. Fuscaldi; Danielle V. Sobral; Ana Claudia R. Durante; Fernanda F. Mendonça; Ana Cláudia C. Miranda; Marcelo L. da Cunha; Luciana Malavolta; Jorge Mejia; Marycel F. de Barboza (MDPI AG, 2021)
Prostate-specific membrane antigen (PSMA) is a glycoprotein present in the prostate, that is overexpressed in prostate cancer (PCa). Recently, PSMA-directed radiopharmaceuticals have been developed, allowing the pinpointing of tumors with the Positron Emission Tomography (PET) or Single Photon Emission Computed Tomography (SPECT) imaging techniques. The aim of the present work was to standardize and validate an automatic synthesis module-based radiolabeling protocol for [68Ga]Ga-PSMA-11, as well as to produce a radiopharmaceutical for PET imaging of PCa malignancies. [68Ga]Ga-PSMA-11 was evaluated to determine the radiochemical purity (RCP), stability in saline solution and serum, lipophilicity, affinity to serum proteins, binding and internalization to lymph node carcinoma of the prostate (LNCaP) cells, and ex vivo biodistribution in mice. The radiopharmaceutical was produced with an RCP of 99.06 ± 0.10%, which was assessed with reversed-phase high-performance liquid chromatography (RP-HPLC). The product was stable in saline solution for up to 4 h (RCP > 98%) and in serum for up to 1 h (RCP > 95%). The lipophilicity was determined as −3.80 ± 0.15, while the serum protein binding (SPB) was <17%. The percentages of binding to LNCaP cells were 4.07 ± 0.51% (30 min) and 4.56 ± 0.46% (60 min), while 19.22 ± 2.73% (30 min) and 16.85 ± 1.34% (60 min) of bound material was internalized. High accumulation of [68Ga]Ga-PSMA-11 was observed in the kidneys, spleen, and tumor, with a tumor-to-contralateral-muscle ratio of >8.5 and a tumor-to-blood ratio of >3.5. In conclusion, an automatic synthesis module-based radiolabeling protocol for [68Ga]Ga-PSMA-11 was standardized and the product was evaluated, thus verifying its characteristics for PET imaging of PCa tumors in a clinical environment.